Mandibular Metastasis of Silent Papillary Thyroid Carcinoma: A Rare Case Report with Review of the Literature - Shahzad Gholami; Mahin Bakhshi; Saede Atarbashi-Moghadam; Hassan Mir Mohammad Sadeghi; Arezoo Rahimzamani (Case Reports in Dentistry)
Metastasis to the jaws is a rare event; however, it has great importance because it may be the only symptom of an undiagnosed underlying malignancy. Papillary thyroid carcinoma, the commonest histopathologic variant of thyroid cancer, has minimal potential for distant metastasis, and most reported metastatic thyroid carcinomas of the oral cavity have been follicular thyroid carcinoma. The aim of this article is to present a rare case of metastatic papillary thyroid carcinoma, which presented itself as a painless expansion in the anterior region of the mandible in a 56-year-old female, and to review previously published cases of this type of cancer. Reporting rare cases such as this one, together with reviewing previous reports of related rare diseases, will expand the body of knowledge about these uncommon lesions.